Antibacterial activity of essential oils on Xanthomonas vesicatoria and control of bacterial spot in tomato - Lucas, Gilvaine Ciavareli; Alves, Eduardo; Pereira, Ricardo Borges; Perina, Fabiano José; Souza, Ricardo Magela de (Pesquisa Agropecuária Brasileira, 2012)
The objective of this work was to evaluate the effects of plant essential oils (EOs) on the growth of Xanthomonas vesicatoria, on bacterial morphology and ultrastructure, and on the severity of tomato bacterial spot. EOs from citronella, clove, cinnamon, lemongrass, eucalyptus, thyme, and tea tree were evaluated in vitro at concentrations of 0.1, 1.0, 10, and 100% in 1.0% powdered milk. The effect of EOs, at 0.1%, on the severity of tomato bacterial spot was evaluated in tomato seedlings under greenhouse conditions. The effects of citronella, lemongrass, clove, and tea tree EOs, at 0.1%, on X. vesicatoria cells were evaluated by transmission electron microscopy. All EOs showed direct toxic effect on the bacteria at a 10%‑concentration in vitro. Under greenhouse conditions, the EOs of clove, citronella, tea tree, and lemongrass reduced disease severity. EOs of clove and tea tree, and streptomycin sulfate promoted loss of electron‑dense material and alterations in the cytoplasm, whereas EO of tea tree promoted cytoplasm vacuolation, and those of citronella, lemongrass, clove, and tea tree caused damage to the bacterial cell wall. The EOs at a concentration of 0.1% reduce the severity of the disease.